Associations Between Multiple Remote Mild TBIs and Objective Neuropsychological Functioning and Subjective Symptoms in Combat-Exposed Veterans. (2nd March 2020) - Merritt, Victoria C; Jurick, Sarah M; Crocker, Laura D; Sullan, Molly J; Sakamoto, McKenna S; Davey, Delaney K; Hoffman, Samantha N; Keller, Amber V; Jak, Amy J
Abstract: Objective: The purpose of this study was to evaluate relationships between multiple mild traumatic brain injuries (mTBIs) and objective and subjective clinical outcomes in a sample of combat-exposed Veterans, adjusting for psychiatric distress and combat exposure. Method: In this cross-sectional study, 73 combat-exposed Iraq/Afghanistan Veterans were divided into three groups based on mTBI history: 0 mTBIs ( n  = 31), 1–2 mTBIs ( n  = 21), and 3+ mTBIs ( n  = 21). Veterans with mTBI were assessed, on average, 7.78 years following their most recent mTBI. Participants underwent neuropsychological testing and completed self-report measures assessing neurobehavioral, sleep, and pain symptoms. Results: MANCOVAs adjusting for psychiatric distress and combat exposure showed no group differences on objective measures of attention/working memory, executive functioning, memory, and processing speed (all p's  > .05; ηp 2  = .00–.06). In contrast, there were significant group differences on neurobehavioral symptoms ( p's =  < .001–.036; ηp 2  = .09–.43), sleep difficulties ( p  = .037; ηp 2  = .09), and pain symptoms ( p  < .001; ηp 2  = .21). Pairwise comparisons generally showed that the 3+ mTBI group self-reported the most severe symptoms, followed by comparable symptom reporting between the 0 and 1–2 mTBI groups. Conclusions: History of multiple, remote mTBIs is associated with elevated subjective symptoms but not objective neuropsychological functioning in combat-exposed Veterans. These results advance understanding of the long-term consequences of repetitive mTBI in this population and suggest that Veterans with 3+ mTBIs may especially benefit from tailored treatments aimed at ameliorating specific neurobehavioral, sleep, and pain symptoms.